2015
DOI: 10.1371/journal.pone.0142063
|View full text |Cite
|
Sign up to set email alerts
|

An Unprecedented High Incidence of Leptospirosis in Futuna, South Pacific, 2004 – 2014, Evidenced by Retrospective Analysis of Surveillance Data

Abstract: Futuna is a small Polynesian island in the South Pacific with a population of 3,612 in 2013. The first human leptospirosis case was confirmed in 1997. Active surveillance started in 2004. Cases were confirmed by PCR or real time PCR, or by serology using MAT or a combination of IgM-ELISA and MAT. A retrospective analysis of surveillance data shows that the disease was endemic with a mean annual incidence of 844 cases per 100,000 over an 11-year period from 2004 to 2014. An epidemic peak as high as 1,945 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Another clinical study conducted in 2005 identified one case in Wallis and 21 cases in Futuna [ 137 ], and reported some exposure information: one case swam in a river few days before the occurrence of the disease, and all the other cases were involved in breeding pigs (at home for the Futuna cases, at work in a pig farm for the one Wallis case). A third study conducted over the period 2004–2014 reported 382 cases in Futuna, with a peak incidence in 2008 [ 7 ]. Serogroup Australis was predominant until 2007, when Icterohaemorrhagiae became the most common.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another clinical study conducted in 2005 identified one case in Wallis and 21 cases in Futuna [ 137 ], and reported some exposure information: one case swam in a river few days before the occurrence of the disease, and all the other cases were involved in breeding pigs (at home for the Futuna cases, at work in a pig farm for the one Wallis case). A third study conducted over the period 2004–2014 reported 382 cases in Futuna, with a peak incidence in 2008 [ 7 ]. Serogroup Australis was predominant until 2007, when Icterohaemorrhagiae became the most common.…”
Section: Resultsmentioning
confidence: 99%
“…Leptospirosis is a neglected disease in most of the tropics, especially in the Pacific region [ 5 ], and a recent systematic review found that Oceania was the region most impacted by leptospirosis in terms of morbidity (150.68 cases per 100,000 per year), mortality (9.61 deaths per 100,000 per year) [ 3 ], and disability adjusted life years (DALY) [ 6 ]. Incidence of up to 1,945 cases per 100,000 population has been reported in 2008 in Futuna (a Polynesian island) during a multi-year outbreak [ 7 ]. The health impacts of leptospirosis have been predominantly attributed to acute infections and early complications such as pulmonary haemorrhage and renal failure.…”
Section: Introductionmentioning
confidence: 99%
“…In the French Caribbean, prospective studies have revealed a higher level of incidence of leptospirosis than previously known. [2][3][4]31 They led health authorities to implant local surveillance network and on-site efficient diagnostic tools and increased local physicians' awareness toward leptospirosis.…”
Section: Discussionmentioning
confidence: 99%
“…2 Incidence in the French overseas departments and territories located in the Pacific and Indian oceans and the Caribbean (Martinique and Guadeloupe) is much higher, up to 36/100,000. 3,4 French Guiana is a French overseas territory located on the northern coast of South America. More than 95% of its surface is Amazonian rain forest.…”
Section: Introductionmentioning
confidence: 99%
“…Experts estimate that annually 1.03 million patients and 58,900 deaths are registered which occur due to leptospirosis among the world population. The highest incidence and mortality is observed in South and Southeast Asia, Oceania, Latin America and East Africa [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%